2008
DOI: 10.1002/pc.20714
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characteristics of out‐of‐plane permeability for plain‐woven structure

Abstract: Since out‐of‐plane permeability of fiber preforms is a function of the number and arrangement of stacked layers, either many layers of preforms or numerous experiments are required to obtain an exact out‐of‐plane permeability experimentally. The reason is that there exist nesting and phase shifting when the preforms are laid up. From a statistical viewpoint, the effect of the number of preform layers on the out‐of‐plane permeability was analyzed by adopting an analytical model proposed in this study. Numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…As long as the position of the flow front at the moment of t, namely (x f , y f ), was known, substitute it into equation (16) and then the primary permeability of the fabrics can be figured out…”
Section: Methodsmentioning
confidence: 99%
“…As long as the position of the flow front at the moment of t, namely (x f , y f ), was known, substitute it into equation (16) and then the primary permeability of the fabrics can be figured out…”
Section: Methodsmentioning
confidence: 99%
“…Ngo and Tamma (2004) predicted the through-thickness permeability of a three-dimensional orthogonal woven fabric based on a detailed geometrical description of the textile unit cell, and found qualitative agreement with experimental observations. Song et al (2009) developed a unit cell based model and performed stochastic analyses for the example of a plain weave fabric. These showed that at a given fi bre volume fraction, but different numbers of layers, the average value is constant but the standard deviation decreases with increasing number of layers.…”
Section: © Woodhead Publishing Limited 2011mentioning
confidence: 99%
“…This is realized by an extremely slight suspension of the lower distribution media, which is moveable. At the beginning of a measurement the distribution media is placed on precisely grounded support discs (14), which allow an exact setting of the pre-compaction. The spring force is so small that even at practically no pre-compaction no movement of the distribution media takes place, prior to the measurement.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…During a saturated measurement a continuous flow through the textile is generated and, according to Eq.1, the pressure drop and the flow velocity (respectively the volume flow rate) are measured. Several of these systems have been developed since 1971 [7][8][9][10][11][12][13][14]. The unsaturated principle requires the monitoring of the flow front progression of a liquid injected into the dry resin.…”
Section: Introductionmentioning
confidence: 99%